A study of the influence of lipid profile in diabetic patients on the incidence of cerebrovascular events - Khalid, Taha Mahboob Ali; G., Rahul Gandhi (International Journal of Advances in Medicine, 2019)
Background: The relationship between elevated serum lipids and atherosclerosis is well established. Recent studies have demonstrated not only that the serum lipid concentration but also the distribution of TG and cholesterol within major lipoprotein classes are of importance for the development of atherosclerosis. Elevated plasma concentrations of LDL and decreased HDL are associated with increased risk of atherosclerosis. To study the influence of lipid profile in diabetic patients on the incidence of cerebrovascular events. Methods: The study was based on 60 patients meeting the inclusion criteria from those who were admitted at Shadan Institute of Medical Sciences, Hyderabad, India from Feb 2013-May 2014. Detailed history was taken and thorough physical examination done pertaining to the involved condition. Patients who were conscious, slow progression of neurological deficit, rapid onset of lateralizing signs with variable blood pressure were considered to be suffering from infarction. Results: The mean values of lipid profile were significantly different among the gender. There were more females with medium and high TC values as compared to females and this difference was found to be significant. Though the number of females with high HDL values was more than males, the difference was not found to be significant. The number of females with high LDL values was far more than males and this difference was found to be significant. Though the number of females was more with high TG values, the difference was not found to be significant. Conclusions: In conclusion, our study gives evidence that poor glycemic control is a strong risk factor for stroke in patients with NIDDM.